2016
DOI: 10.1242/dev.132175
|View full text |Cite
|
Sign up to set email alerts
|

JNK signaling regulates E-cadherin junctions in germline cysts and determines primordial follicle formation in mice

Abstract: Physiologically, the size of the primordial follicle pool determines the reproductive lifespan of female mammals, while its establishment largely depends on a process of germline cyst breakdown during the perinatal period. The mechanisms regulating this process are poorly understood. Here we demonstrate that c-Jun amino-terminal kinase (JNK) signaling is crucial for germline cyst breakdown and primordial follicle formation. JNK was specifically localized in oocytes and its activity increased as germline cyst b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
29
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 46 publications
(23 reference statements)
4
29
0
Order By: Relevance
“…Recent studies have implied that inhibition of JNK enhances Ecadherin redistribution to plasma membrane and promotes adherens junctions formation (16,17). Niu et al (18) show that JNK regulates E-cadherin degradation through the E3 ubiquitin ligase MDM2. In addition to evidence that JNK regulates E-cadherin redistribution and stability, our data reveal JNK suppression of E-cadherin expression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have implied that inhibition of JNK enhances Ecadherin redistribution to plasma membrane and promotes adherens junctions formation (16,17). Niu et al (18) show that JNK regulates E-cadherin degradation through the E3 ubiquitin ligase MDM2. In addition to evidence that JNK regulates E-cadherin redistribution and stability, our data reveal JNK suppression of E-cadherin expression.…”
Section: Discussionmentioning
confidence: 99%
“…While JNK has been shown to play an important role in regulating E-cadherin junctions (16)(17)(18), the effect of TRAF2 on E-cadherin expression has not been studied.…”
mentioning
confidence: 99%
“…To future confirm nZnO toxicity on pregnant mice, the germ cell number at 17.5 dpc (germ cells arrived in diplotene of MPI), 3 dpp (ovarian reservior establishment), 21 dpp (puberty), and 4 - 6 weeks (adult) [ 34 , 35 ] was compared. It was found that nZnO exposure increased the accumulation of DSBs in 17.5 dpc fetal oocytes.…”
Section: Discussionmentioning
confidence: 99%
“…This Ecadherin decrease is an effect of JNK signaling. The in vitro inhibition of this signaling pathway enhanced the expression of E-cadherin and disrupted cyst breakdown [46]. On the other hand, the in vitro inhibition of E-cadherin accelerated cyst breakdown and primordial follicle formation.…”
Section: Cadherins In Gonad Developmentmentioning
confidence: 95%
“…In the developing ovaries, during the cyst breakdown, specific changes in E-cadherin expression occur. In mice, E-cadherin is initially intensively located at oocyte-oocyte contacts until E17.5, and after that time, the localization of E-cadherin becomes weaker and diffused [46]. The expression of E-cadherin again increases by P4.…”
Section: Cadherins In Gonad Developmentmentioning
confidence: 99%